2019
DOI: 10.18332/tpc/111536
|View full text |Cite
|
Sign up to set email alerts
|

State-specific cigarette use rates among service members and veterans, United States, 2017

Abstract: INTRODUCTION Little is known about the geographical distribution of cigarette use among military service members and veterans. In this study, we estimated statespecific rates of current cigarette use for service members and veterans and compared these to the current cigarette use rates of civilians. METHODS We used data from the 2017 Behavioral Risk Factor Surveillance System to generate survey-weighted percentages with 95% confidence intervals of current cigarette use among service members and veterans (SMVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Our analysis revealed that cigarette use may be less prevalent among military parents than in previous reports, potentially due to the implementation of military smoke-free policies 8,9 and other local-related factors, such as locally influenced differences. 17 Furthermore, our findings align with existing literature in that older age [18][19][20] may be associated with increased risk for cigarette use.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis revealed that cigarette use may be less prevalent among military parents than in previous reports, potentially due to the implementation of military smoke-free policies 8,9 and other local-related factors, such as locally influenced differences. 17 Furthermore, our findings align with existing literature in that older age [18][19][20] may be associated with increased risk for cigarette use.…”
Section: Discussionsupporting
confidence: 90%
“…Our adjusted analysis also identified being a veteran as a novel factor associated with increased odds of screening. Veterans have higher smoking rates than their nonveteran peers, and Veterans Health Administration (VHA) hospitals have been sites for lung cancer screening interventions, which may play a role in the increased lung cancer screening uptake 35,36 . Notably, more than half of eligible VHA patients agreed to undergo screening at eight demonstration sites between 2013 and 2015 36 .…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Veterans are at increased risk of lung cancer, given high rates of tobacco use, with a large population of veterans eligible for LCS. 17,18 Although the Veterans Health Administration (VHA), the largest national integrated health care system in the US, was an early adopter of LCS, subsequent implementation has been inconsistent across VHA facilities. 19 Thus, the VHA provides an ideal realworld setting to study adherence after initial LCS across the US.…”
Section: Introductionmentioning
confidence: 99%